Development of Student’s Worksheet using Project-Based Learning (PjBL) on Ecosystem Concept for Class X SMA - Riana, Febi; Sunarto, Sunarto; Mamangkey, Jendri (Bioeduca : Journal of Biology Education, 2024)
The students' learning interest is decreasing due to the lack of interactive, enjoyable, and supportive instructional materials to help them achieve good learning outcomes. Therefore, researchers innovated by developing Learner Worksheets (LKPD) based on Project-Based Learning (PjBL). The research aims to assess the feasibility of PjBL-based LKPD through evaluations from experts (in content, media, and language) and students' responses. The research type used is Research and Development (R&D). The assessment results from content experts showed a score of 82.03% "Very Feasible," media experts rated it 86.5% "Very Feasible," and language experts rated it 83% "Very Feasible," while students' response was 53% "Fairly Positive." Thus, it can be concluded that PjBL-based LKPD is feasible and can be used in education, especially in the field of biology